(untitled) (Baghdad Science Journal, 2021)
This study was conducted to investigate thyroid function and Anti-Müllerian hormone (AMH) in (Chronic kidney disease) CKD patients by evaluating their levels in CKD patients, 50 patients were diagnosed to have CKD stage-5, their ages ranged between 20-50 years (25 males and 25 females) who attended the Nephrology and Transplant Center in Medical City of Baghdad- Iraq, they were recruited from April 2018 to July 2018 and were enrolled into the study. The control group consisted of 20 healthy individuals, their ages ranged between 20-48 years (10 males and 10 females). The study showed non-significant (p>0.05) increase in AMH level in CKD patients compared to the control group. On the other hand, TSH was recorded a highly significant (P<0.01) increase in CKD patients in comparison with control. While T3 and T4 levels recorded highly significant (P<0.01) decrease in CKD patients in comparison with control.